The dynamic plasticity of insulin production in β-cells - Brandon B. Boland; Christopher J. Rhodes; Joseph S. Grimsby (Elsevier, 2017)
Background: Although the insulin-producing pancreatic β-cells are quite capable of adapting to both acute and chronic changes in metabolic demand, persistently high demand for insulin will ultimately lead to their progressive dysfunction and eventual loss. Recent and historical studies highlight the importance of 'resting' the β-cell as a means of preserving functional β-cell mass. Scope of Review: We provide experimental evidence to highlight the remarkable plasticity for insulin production and secretion by the pancreatic β-cell alongside some clinical evidence that supports leveraging this unique ability to preserve β-cell function. Major conclusions: Treatment strategies for type 2 diabetes mellitus (T2DM) targeted towards reducing the systemic metabolic burden, rather than demanding greater insulin production from an already beleaguered β-cell, should be emphasized to maintain endogenous insulin secretory function and delay the progression of T2DM.